Aldol Condensations Catalyzed by Basic Anion‐Exchange Resins. Issue 23 (4th November 2016) - Bonrath, Werner; Pressel, Yann; Schütz, Jan; Ferfecki, Erich; Topp, Klaus‐Dieter
Abstract: The aldol condensations of various aldehydes with ketones in the presence of anionic (basic) ion‐exchange resins have been investigated. Both batch and continuous modes were studied and compared for the reaction of citral (a mixture of geranial and neral) with acetone to give ψ‐ionone. Different reaction conditions were investigated, and the performances of five different ion‐exchange resins were compared. The most stable resins could be used for 10 cycles in batch mode or 1000 min in continuous mode without a significant loss in activity or selectivity. Abstract : Ion‐exchange resins in catalysis : Solid bases applied in aldol condensations avoid the formation of waste. Batch and continuous modes were studied for a variety of terpenoids. The most stable resins could be used for 10 cycles in batch mode or 1000 min in continuous mode without a significant loss in activity or selectivity.